Electrical Network Protection System on The Cilegon-Cibinong Conductor Using A Defense Scheme with Over Generation Shedding (OGS) at PT PLN (Persero) UIP2b JAMALI - Febiola Pardede, Devi (Journal of Emerging Supply Chain, Clean Energy, and Process Engineering, 2024)
A Defense Scheme is a protection mechanism designed to normalize the frequency by reducing load or generation. It serves as a safeguard for electrical facilities, access control for system management, routine maintenance to ensure the security and reliability of power system operations, and even as a pre-planned crisis management tool to address emergencies and disturbances in the electrical system. Several types of defense schemes are employed to address or prevent overload shedding (OLS) and Oover generation shedding (OGS). With the rapid advancements in technology, particularly in the industrial sector, innovative solutions have become increasingly sophisticated. One example is the maintenance system for power plants, which can be optimized through the creation of an operational plan (RENOP) aimed at enhancing efficiency and performance. This includes analyzing the design of electrical network protection systems using the Defense Scheme for over generation shedding (OGS).